Implementasi Nilai-Nilai Akhlak Dalam Ibadah Shalat Sebagai Upaya Penguatan Pendidikan Karakter Peserta Didik - Azka Khairunnisa; Fatimahtu Zahra; Siti Idah Khoridah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2026)
This study aims to describe in depth how prayer (shalat) functions as a transformative instrument in internalizing moral values and character education for students. This type of research is qualitative descriptive in the form of literature research. The approach used includes an integrative approach between Islamic education and the psychology of religion. Primary data are sourced from authoritative Islamic texts and relevant educational scientific journals, while secondary data include supporting books, which are then processed and analyzed using the content analysis method. The results show that prayer performed with full awareness and thuma'nīnah is able to act as a medium to prevent deviant behavior or abominable and unjust deeds. The implementation of moral values in prayer is manifested through the formation of time discipline character, reduction of negative emotions, training in mature thinking (not in haste), and cultivating humility (tawāḍu‘) in social interaction.